Seismic exploration of hydrocarbons in heterogeneous reservoirs : new theories, methods and applications - Ba, Jing (Elsevier Ltd., 2015)
Seismic Exploration of Hydrocarbons in Heterogeneous Reservoirs: New Theories, Methods and Applications is based on the field research conducted over the past decade by an authoring team of five of the world's leading geoscientists. In recent years, the exploration targets of world's oil companies have become more complex. The direct detection of hydrocarbons based on seismic wave data in heterogeneous oil/gas reservoirs has become a hot spot in the research of applied and exploration geophysics. The relevant theories, approaches and applications, which the authors have worked on for years.